Unfolding island ecologies - (:unkn) unknown (Taideyliopiston Kuvataideakatemia, 2025)
Unfolding Island Ecologies brings together a collection of essays by artists, curators, and researchers reflecting on contemporary environmental and artistic practices. Set against the backdrop of the Helsinki Biennial 2025, the texts explore themes such as ecological interdependence, extractivism, food waste, material cycles, and the agency of non-human entities. Through case studies, fieldwork, and artistic projects, the contributors examine how islands, both literal and metaphorical, serve as sites for imagining sustainable futures. Together, these contributions offer insights into the challenges and possibilities of working with and within fragile ecological contexts across different disciplines and geographies. Contributors: Vera Boitcova, Frank Brümmel, Gua Khee Chong, Alves Ludovico, Blanca de la Torre, Katrin Enni, Jack Faber, Orla Mc Hardy, Katinka van der Jagt, Kati Kivinen, Berenike Melchior, and Rut Karin Zettergren.
Introduction / Samir Bhowmik, Kati Kivinen, and Blanca de la Torre Island as a Shelter / Kati Kivinen and Blanca de la Torre Isolation, Escape, Prestige: Transporting Artworks to Island Locations for Temporary Exhibitions / Frank Brümmel On Food and Conversations about Food / Gua Khee Chong Home as an Ecosystem: The Ecology of Queer Migrant Narratives / Vera Boitcova From Supernova to E-Waste: Tracing the Lifecycle of Copper / Katrin Enni Visiting the Diatoms / Berenike Melchior Postscript on States of Security / Jack Faber The Splitting Ambition / Alves Ludovico Memories of Planet: What if not central to Universe? / Katinka van der Jagt The Soil, the Ocean and the Sample / Rut Karin Zettergren Turning the Heap / Orla Mc Hardy Bibliography Biographies.
Keywords: Helsinki Biennial 2025; taide; nykytaide; taiteellinen työ; taiteellinen tutkimus; kestävä kehitys; ekologia; art; contemporary art; artistic work; artistic research; sustainable development